Reproductive behavior of the swimming crab Arenaeus cribrarius (Lamarck, 1818) (Crustacea, Brachyura, Portunidae) in captivity - Pinheiro, Marcelo Antonio Amaro [UNESP]; Fransozo, Adilson [UNESP] (My University, 1999)
In this study, the reproductive behavior exhibited by Arenaeus cribrarius in captivity was described, and the duration of each behavioral stage was measured. Swimming crabs were trawled in Ubatuba, northern littoral of São Paulo State, Brazil, and maintained in aquaria. Water conditions and food items were provided according to this species' natural requirements in the wild. In the presence of premolt females, intermolt males exhibited a courtship display that became intensified when the potential mate was visually perceived. After mate selection, the male carried the female under itself (precopulatory position) for 29.8 ± 5.1 d until the female molted. Afterwards, the male manipulated the recently molted female, and inverted her position under itself as to penetrate her with his first pair of pleopods (copulation), a process that took 17.1 ± 4.6 h. After copulation the male continued to carry his soft-shelled mate for 29.7 ± 5.8 d (postcopulatory position). The time elapsed between copulation and spawning was 57.8 ± 3.8 d, and the time interval between successive spawns 33.8 ±7.1 d. Total embryonic development took 13.5 ± 2.1 d in temperature conditions of 25.0 ±2.0° C. During the last 4.7 ± 1.4 d, embryos' eyes were already visible. The reproductive behavior pattern in A. cribrarius is very similar to those previously described in other portunids.